Corporate Sustainability Reporting in Southeast Asia: A Scoping Review - Kono, Videl Remus; Restuningdiah, Nurika; Juliardi, Dodik (Journal of Applied Business, Taxation and Economics Research, 2023)
This research aims to map developments, factors and theories used in corporate sustainability reporting in Southeast Asia. The method used is a scoping review adopted from Arksey & O'Malley. Use of secondary data from six databases, namely Sage, Wiley, Emeral, Taylor & Francis, Springer and Proquest. The scope of this research is countries in the Southeast Asia region with an observation period of eight years (2015-2023). The results obtained were 40 articles which illustrate that companies in Southeast Asia generally have implemented sustainability in their reports but it is voluntary but companies that have registered on the stock exchange are mandatory. The country with the most research is Indonesia, while the least or none is Cambodia, Myanmar and Laos. It was found that 8 factors influence sustainability reporting in Southeast Asia and 12 theories used, where the most dominant are legitimacy theory and stakeholder theory, the most published articles are in the Emeral database, the most used method is quantitative, the year of most publications is 2023, There are 6 journals with quality A and 12 journals with quality B. Social Responsibility Journal is the dominant journal with 7 articles.